VOLCANICLASTIC DEPOSITS FROM THE NORTH ARCH VOLCANIC FIELD, HAWAII: EXPLOSIVE FRAGMENTATION OF ALKALIC LAVA AT ABYSSAL DEPTHS - Davis A.S.; Clague D.A. (My University, 2006)
Submarine explosive eruptions are generally considered to become less likely with increasing depth due to the increasing hydrostatic pressure of the overlying water column. Volcaniclastic deposits from the North Arch volcanic field, north of Oahu, have textural characteristics of explosive fragmentation yet were erupted in water depths greater than 4,200 m. The most abundant volcaniclastic samples from North Arch are clast-supported with highly vesicular, angular pyroclasts. They are most likely near-vent pyroclastic fall deposits formed in eruption columns of limited height. Interbedded with highly vesicular pillow lava, they form low (50 to 200 m), steep-sided cones around the vents. Less common are stratified samples with graded bedding; one such sample includes a layer of roughly aligned, platy, bubble-wall glass fragments (resembling littoral limu o Pele) that may have been deposited by density currents. In addition to bubble-wall glass shards, numerous glass fragments with spherical, delicate spindle and ribbon shapes, and Pele's hair-like glass strands occur in the finer size fraction (<0.5 mm) of some samples. They are probably more distal fallout. Another sample, consisting of glass fragments dispersed in a marine clay matrix, was apparently reworked and deposited farther from the vents by bottom currents. Glass compositions include low-(~0.4-0.6 wt%) and medium-K2O (>0.6 wt%) alkalic basalt, basanite, and nephelinite. Sulfur and chlorine abundances are high, reaching a maximum of 1,800 and 1,300 ppm, respectively. The ubiquitous presence of limu o Pele fragments, regardless of glass composition, suggests that bursts of Strombolian-like activity accompanied most eruptions. Coalescing vesicles observed in larger pyroclasts and some pillow lava suggests accumulation of volatiles. Since the great hydrostatic pressure makes steam expansion impossible, a volatile-rich, supercritical magmatic fluid probably drove the eruptions. If these volatile-rich magmas had erupted in shallow water or subaerially, tall fountains would most likely have resulted. The great hydrostatic pressure (>40 MPa) limited fountain and eruption column heights.
Keywords: SUBMARINE EXPLOSIONS; STROMBOLIAN; PYROCLASTIC FRAGMENTATION; LAVA BUBBLE WALL FRAGMENTS; ALKALIC BASALT; NORTH ARCH VOLCANIC FIELD; HAWAII